Visceral Leishmaniasis in Muzaffarpur District, Bihar, India from 1990 to 2008 - Malaviya, Paritosh (Public Library of Science, 2011)
BACKGROUND: Visceral Leishmaniasis (VL) is a vector-borne disease transmitted by Phlebotomus argentipes. To understand the VL seasonality, annual and monthly variations of VL incidence and its relationship to meteorological variables, the numbers of VL cases reported in Muzaffarpur district, Bihar, India from 1990 to 2008 were studied. METHODS: Annual VL incidence per 10,000 and the total number of annual VL cases reported at block Community Health Centres (CHC), Public Hospitals or Non-Governmental Organisations (NGO) and the number of VL cases per month from 2000 to 2008 as well as the monthly average of cases for 2000–08, 2000–04 and 2005–08 periods along with the monthly averages of temperature, rainfall and relative humidity were plotted. VL Standardised Incidence Ratios per block were computed for the periods of 1990–1993, 1994–1998, 1999–2004 and 2005–2008 and month wise from 2002 to 2008. A negative binomial regression model was used to evaluate the association between meteorological variables and the number of VL cases per month from 2000 to 2008. RESULTS: A total of 68,358 VL cases were reported in Muzaffarpur district from 1990 to 2008, ranging from 1,2481 in 1992 to 1,161 in 2001. The blocks with the highest number of cases shifted from East (1990–98) to West (1999–2008). Monthly averages of cases ranged from 149 to 309, highest peak in March–April and another one in July. Monthly VL incidence was associated positively to rainfall and negatively to relative humidity and the numbers of VL cases in the previous month. INTERPRETATION: The number of cases reported to the public health sector allowed the describing of the spatial distribution and temporal variations in the Muzaffarpur from 1990 to 2008. However, to assess the actual VL burden, as well as the efficacy of the control measures applied in the district, reporting from private practices and NGOs should be encouraged.